Effects of quorum sensing and its degrader on the virulence of Vibrio harveyi towards tiger grouper, Epinephelus fuscoguttatus Forsskal larvae - Md. Noor, Noorashikin (2015)
Quorum sensing (QS) is a bacterial cell-to-cell communication with small signal molecules such as acyl-homoserine lactones (AHL) that control a number of phenotypes including the regulation of virulence determinants in pathogenic bacteria. Therefore, quorum sensing degrader has been suggested as one of the biocontrol strategy to fight bacterial infections as an alternative to the use of antibiotics. In this study, the link between quorum sensing (QS) in Vibrio harveyi and its virulence towards tiger grouper (Epinephelus fuscoguttatus) were investigated. The virulence activity was studied using V. harveyi wild type and its QS mutants with constitutively maximal or minimal quorum sensing activity and different signal molecule (autoinducer) synthase gene mutants. The potential of live feed Artemia as the carrier of bacterial quorum sensing degrader for the tiger grouper larvae was also investigated. The results showed that the wild type Vibrio harveyi BB120 was pathogenic to grouper (Epinephelus fuscogutattus) larvae causing more than 50% larval mortality after four days of challenge. Furthermore, the mortality of grouper larvae challenged withV. harveyimutant JAF483 with maximally active QS (QS+) was significantly higher than the V. harveyiwild type BB120. Meanwhile, high survival was observed in the grouper larvae challenged to JAF548 with minimally active QS (QS-) compared to the JAF483 (QS+). High survival of larvae were also observed in the QS autoinducer mutant strains of JMH634 (QS triple autoinducer synthase mutant),BB152 (Harveyi autoinducer-1 (HAI-1) synthase mutant) and MM30 (Autoinducer-2 (AI-2) synthase mutant). In contrast, low survival was observed in the strain JMH603 (Cholerae autoinducer-1 (CAI-1) synthase mutant). This indicated that the HAI-1 and AI-2 QS signal molecules might play important roles for the virulence of V. harveyi towards grouper larvae but not CAI-1. To support this, addition of HAI-1 in the water restored the virulence of the mutant. The effects of the infection on the larvae could also be seen histologically. In addition, the in vivo expression data showed that the HAI-1 signal molecule upregulated the innate immune genes consisting of tripartite motif-containing protein 39 (TRIM39), Hepcidin-1 (Hep-1), peptidoglycan recognition protein SC2 (PGRP) and toll like receptor 5 (TLR5) at different hours compared to control. The expression of both control and the bacterial mutant BB152 without HAI-molecules remained low throughout the experimental period. Next, different bacterial QS degrader strains were isolated from Artemia and screened using Chromobacterium violaceum CV026 bioassay. The results showed six bacterial strains (four Gram-positive and two Gramnegative) isolated from Artemia are able to degrade AHL in two different in vitro assays. The highest bacterial AHL degrader, identified as Bacillus litoralis BP-ART/6 fully degraded 10 ppm AHL from 9 hours. Encapsulation of the Bacillus strain to Artemia also significantly improve the survival and total length of the live feedcompared to control without addition of any bacteria. This study showed that bacterial strain isolated from Artemia can act as a quorum sensing degrader and can be encapsulated to Artemia. It was later observed that B. litoralis could also be used as probiotic bacteria administered through Artemia nauplii to protect grouper larvae against infection of V. harveyi.